Jual Beli melalui E-Commerce dalam Pandangan Hadis: Studi Takhrij dan Syarah Hadis - Hasan Muhammad Al Fatih (Gunung Djati Conference Series, 2022)
This study aims to discuss the Hadith about labor in buying and selling through e-commerce. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about hard work in Imam al Bukhari's narration No. 1930. The results and discussion of this study indicate that the status of the hadith is of saheeh quality that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the Hadith narrated by Bukhari No. 6832 is relevant to be used as a basis for buying and selling through e-commerce while still paying attention to the aspects of labor and prudence so that they are in accordance with Islamic law.